ENHANCING BUSINESS PROFITS THROUGH FINANCIAL MANAGEMENT TRAINING AT RUFATA MSMEs - Indriyarti, Eko Retno; Astuti, Henik Hari; Lenggogeni, Lenggogeni (Jurnal Pengabdian dan Kewirausahaan, 2024)
Micro, small, and medium enterprises (MSMEs), particularly in the culinary sector, frequently grapple with the challenge of effectively recording and managing both business and personal finances. This led to the initiation of community service activities that focused on the topic of financial management. The decision to focus on this topic was made to maximize business profits. The objective of this event, scheduled for March 2024, is to augment the knowledge and expertise of Rufata MSME participants engaged in the culinary industry in Gudang Sarinah, Pancoran, and South Jakarta. We utilize training techniques to accomplish this endeavour. This activity encompasses the procedure of recording and overseeing a business's revenue and expenses. The objective is to furnish business proprietors with precise and all-encompassing data regarding their financial circumstances. Furthermore, this PKM seeks to aid commercial entities in differentiating between business funds and personal resources. The exercises conducted demonstrated that all participants derived benefits from the provided knowledge, particularly due to its straightforward adoption and practical application. Furthermore, the participants assessed whether the provided material aligned with their requirements and whether its delivery was clear. Moreover, the participants expressed their readiness to participate in future attempts, emphasizing the benefits they experienced from the current actions.